2019
DOI: 10.2147/opth.s217930
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anterior chamber angle in aniridia with and without glaucoma</p>

Abstract: Purpose We performed a retrospective, comparative study to determine if patients with aniridia and glaucoma had open angles on high-resolution anterior segment optical coherence tomography (OCT) and clinical gonioscopy. Patients and methods Forty-three patients (86 eyes) with aniridia had recorded anterior segment OCTs, gonioscopy, or both. Of these patients, 27 (54 eyes) were diagnosed with glaucoma and 16 (32 eyes) had no evidence of glaucoma. All patients had either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…We have even been able to image emulsified silicon oil droplets in the AC, subconjunctivally and adherent to the anterior lens capsule. Bajwa et al 20 have studied aniridia with this technique in 43 patients, some of them were children. Ahmed 21 et al have utilized this technique in 9 children with mucopolysaccharidoses and found it useful to predict glaucoma risk, and also observed crowded anterior segments and thick corneas in these.…”
Section: Discussionmentioning
confidence: 99%
“…We have even been able to image emulsified silicon oil droplets in the AC, subconjunctivally and adherent to the anterior lens capsule. Bajwa et al 20 have studied aniridia with this technique in 43 patients, some of them were children. Ahmed 21 et al have utilized this technique in 9 children with mucopolysaccharidoses and found it useful to predict glaucoma risk, and also observed crowded anterior segments and thick corneas in these.…”
Section: Discussionmentioning
confidence: 99%
“…There are several research data confirming a direct correlation of PAX6 gene mutation with aniridia occurrence [181][182][183][184]. Interestingly, it has been reported that aniridia is frequently correlated with glaucoma and glaucoma associated with aniridia may trigger a progressive loss of vision [185]. Netland et al have reported that, in 46% individuals, out of 83 aniridia subjects, glaucoma has been identified [186].…”
Section: Ntf4mentioning
confidence: 94%
“…Other recognised mechanisms are progressive angle closure with peripheral anterior synechiae and aniridia fibrosis syndrome secondary to intraocular surgeries. [4][5][6][7][8] Congenital glaucoma associated with or without buphthalmos is rare in aniridia. [5][6][7] The ocular phenotype can vary between and within families in aniridia, but affected individuals usually have similarity between the two eyes.…”
Section: Images In…mentioning
confidence: 99%
“…[4][5][6][7][8] Congenital glaucoma associated with or without buphthalmos is rare in aniridia. [5][6][7] The ocular phenotype can vary between and within families in aniridia, but affected individuals usually have similarity between the two eyes. 1 Asymmetry of ocular phenotype is not a rarity in syndromic cases and has been reported in the literature.…”
Section: Images In…mentioning
confidence: 99%